Growth of rhizopus oligosporus in sago effluent at different nitrogen concentration - Shahirah Safin, binti Amran (Universiti Malaysia Sarawak (UNIMAS), 2015)
There are increasing concerns over the pollution created by sago effluent. Fortunately, biotechnological treatment of sago effluent wastewater can yield valuable products while also purifying the sago effluent. In this study, we reported the growth rate of Rhizopus oligosporus in sago effluent at 0, 25, 50 and 100 mM nitrogen concentration via submerged fermentation (SMF). The highest biomass production of the fungus was notable at 100 mM nitrogen concentration which was 84.47 g/L for wet biomass and 3.83 g/L for dry biomass followed by 50, 25 and 0 mM NO3-. These phenomena may be explained that a higher nitrogen concentration resulted in fast fungal cell growth leading to a higher biomass production. The phenol sulfuric test showed carbohydrate concentration fell as growth proceed. Reduction in phenol concentrations by day 6 reached 95% with nitrogen concentration of 100 mM. The study showed the total nitrate and nitrite in the sago effluent decreased gradually after 6 days of fermentation. In 100 mM NO3-, the nitrate and nitrite concentration was reduced from 0.984 to 0.271 g/L and 0.194 to 0.032 g/L, respectively. This result proved the promising applicability of R. oligosporus to treat and purify sago effluent via biological processes. The study have shown that the biomass produced possesses a high protein value and can be used as a better choice for high protein fungal biomass (HPFB) production using inexpensive energy sources like sago effluent.